Antecedents and Consequences of Consumers’ Participation in Online Communities - Zohreh Dehdashti Shahrokhi; Pedram Behyar (مطالعات مدیریت کسب و کار هوشمند, 2017)
Virtual communities are very impressive in the activities associated with the business and broad access to consumers. In this regard, providing the antecedents and consequences of consumers' participation in virtual communities can be effective in the competitive environment from the cognitive aspects of consumer behavior. The purpose of this study is considering the antecedents and consequences of consumers’ participation in virtual communities. The research method was mixed one in a way that in the qualitative section semi-structured interviews with 14 experts was performed and after analyzing the results using the content analysis technique, the designed model in the sample size of 384 persons was tested quantitatively. The results of this study showed that individual and social backgrounds, services provided by the web site, our willingness, attitude and intentions have a significant impact on participation. Considering the implications of participation, we-intentions to participate in virtual communities have a negative impact on communication with family and friends, as well as less use of other media, but increases consumer information.v